(untitled) (AACINI - International Journal of Industrial Engineering, 2020)
The process of social isolation put into manifest the need of generating innovative answers to face different situations. This change of world paradigm has revealed that the linking collaboration of various agents results into more efficiency and effectiveness than searching answers in a dissociated way. That’s the reason why the linking of the academic-scientific with public health has been able to solve the lack of resources and equipment. The link between the State with private business has worked to find smart solutions to the unproductive months. In all of these processes, solidarity and commitment, both individually and collectively, has been the fundamental factor that allowed to flatten the contagion curve and attend to the needs of vulnerable groups, among the most relevant issues. Within the framework of a research in development in collaboration between teachers of engineering schools from Universidad Nacional de Salta (UNSa) and Universidad Nacional de Misiones (UNaM), has been possible to contribute with intermediate entities in the task of information gathering and opportunities to firms and organizations that depend on them. Such was the case of the collaborative work between the researching team with three other institutions: Union Industrial de Salta (UIS); APPES and Municipalidad de Salta. With every institution we had worked collaboratively to complete information referred to geolocation of industries and shops, and make the most of this kind of data in the generation of opportunities for this time of social isolation.